Refining animal welfare of wild boar (Sus scrofa) corral-style traps through behavioral and pathological investigations - Westhoff, Katharina M.; Fetzer, André; Schwan, Zarah; Büttner, Kathrin; Lang, Johannes; Lierz, Michael; Justus Liebig University Giessen (My University, 2024)
Wild boar trapping has been used as a management tool to control wild boar populations. However, it is increasingly criticized due to animal welfare concerns. While cortisol levels have been used to assess trap-related stress in wild boar, data on trap-related injuries and behavioral data are scarce. We aimed to evaluate three different corral-style traps for wild boar according to available mammal trapping standards to investigate and refine animal welfare in wild boar trapping. We examined 138 wild boars captured and killed by head shot in 27 capture events. Traps were closed by remote control only if the complete group were trapped. The behavior of the animals in the trap and during culling was recorded on video. All wild boars were examined and a pathological and radiological examination of the heads for trap- and shot-related injuries followed. Trap-related injuries occurred in 33% of the animals with superficial mild skin defects to skull fractures. One out of three traps met all the set requirements. A wire-meshed trapping system failed all. After installing an incomplete barrier in the center of the trap to slow down trapped animals, the fracture rate in one trap type was significantly reduced by 29% (p < 0.05). Our data showed that the type of trap (p = 0.007) and the number of animals trapped at once (p = 0.002) had a significant influence on the number of escape attempts. Trapping larger groups reduced the escape attempts. We emphasize the importance of an accurate pathological examination to evaluate animal welfare in traps and call for adjusting the injury categories listed in the standards and make a proposal for wild boar live trapping.
Keywords: ddc:630